Effect of occlusal vertical dimension on swallowing patterns and perioral electromyographic activity. (29th March 2016) - MacAvoy, S. K.; Jack, H. C.; Kieser, J.; Farella, M.
Summary: Abnormal swallow patterns have been associated with specific dentofacial traits, such as an anterior open bite, but the cause–effect relationship between swallowing and malocclusion remains highly controversial. The aim of this research was to determine the effects of acute change in occlusal vertical dimension (OVD) on intraoral pressure swallow patterns and perioral electromyographic activity (EMG) during swallowing. Ten volunteers (five female, five male; 27–32 years) repeated standardised swallowing tasks as the OVD was progressively increased using mandibular trays of different heights. Standardised swallowing tasks were performed repetitively with each tray in place. Individual swallowing waveforms were quantitatively and qualitatively analysed. Peak pressure, swallow duration, time to peak pressure and lip EMG peak activity were assessed for each swallow. Data were analysed using mixed‐model analysis. As OVD increased, lip peak pressure during swallowing increased almost threefold (+2·1 kPa; P ≤ 0·001), whereas swallow duration increased by 12·7 per cent (+160 ms; P = 0·01) at lip level and by 26·4 per cent (+270 ms; P < 0·001) at tongue level. Perioral muscle activity during swallows increased by 43·7 per cent ( P ≤ 0·01) up to the OVD where resting lip seal was not attainable. Swallowing waveforms varied markedly between individuals, but interindividual waveforms were only minimally affected. The adaptive response and the waveform similarities associated with OVD variation supports the existence of a central control mechanism for swallowing, which may be modified by peripheral inputs.